Reporte de caso: Mioma Vaginal Gigante: Case report: Giant Vaginal Mioma (La U Investiga, 2020)
BACKGROUND: Uterine leiomyoma’s are among the less frequent gynecological tumors found in gynecological practice, with the literature reporting only about 300 cases worldwide.CLINICAL CASE: We report a 35-year-old patient who attends the outpatient gynecology consultation at the IESS Ibarra Hospital for presenting a tumor mass at the pelvic level and large external genitalia that causes urgency to the point of needing a bladder catheterization to solve the symptoms. The ultrasound studies carried out on the patient offered many diagnostic possibilities from adnexal mass to uterine myoma,but the diagnosis of vaginal myoma was never considered. The patient in her evolution never reported episodes of abnormal Uterine Bleeding, but she did report an important urinary problem characterized by urinary urgency.
Keywords: Uterine leiomyoma; vaginal myoma; Bladder tenesmus